Factors Affecting Micro and Small Industry Income in Tangerang Regency, Banten Province, Indonesia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Micro, small and medium enterprises are one of the pillars of the Indonesian economy. The development andsustainability of MSMEs was determined by several factors. The role of the government and the cooperation of financialinstitutions is one way to increase economic growth. In addition to the role of the government, it required support frominstitutions and other things such as capital support, regulations that favor business actors. Strengthening MSMEs wasimportant in order to be able to increase economic growth. The purpose of this study wa to describe the effect of people'sbusiness credit, investment, and marketing strategies on the income of the MSME industry in the Tangerang district ofIndonesia. This research used quantitative methods. Assumption tests that were carried out include tests for normality,reliability, multicolliarity, heteroscedasticity, multiple analysis, multiple regression coefficients and multiple regressionanalysis. The results showed that there was an influence of people's business credit on the opinion of the MSME Industry, therewas an influence of investment on the opinion of the MSME Industry, there was an influence of marketing strategy on theincome of the MSME Industry, and there was an effect of the influence of the people's business credit, investment, andmarketing strategy together on industrial income. MSMEs in Tangerang district, Indonesia